Literature and Melancholy in the Renaissance (BEOIBERISTIKA - Časopis za iberijske, latinoameričke i komparativne studije (ISSN: 2560-4163 Online), 2025)
This article examines the transformation of the concept of melancholy during the Renaissance, aiming to trace its transition from a medieval perspective—associated with sin and illness—to a modern conception linked to introspection, creativity, and individual consciousness. Through an interdisciplinary approach centered on the analysis of literary and philosophical texts, along with some artistic references, the study explores the main lines of symbolic evolution of melancholy across different European cultural traditions. The article concludes that Renaissance melancholy becomes a hallmark of the modern subject: an affective state that reveals both human fragility and spiritual depth, expressed in literature and art as a path to knowledge and existential inquiry.
Keywords: melancholy; Renaissance; literature; Europe; art and emotions